(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Poverty in India remains one of the most enduring socio-economic challenges, deeply entrenched in a complex interplay of historical, structural, and demographic factors. The legacy of colonial exploitation left behind skewed land ownership patterns, underdeveloped infrastructure, and widespread deprivation, which were further compounded by post- independence issues such as unequal resource distribution, agrarian distress, rapid population growth, and periodic economic shocks. For decades, large segments of the population— particularly in rural areas and among marginalized communities like Scheduled Castes, Scheduled Tribes, and women—have grappled with income insecurity, limited access to education and healthcare, and vulnerability to climate and market fluctuations. Although India has recorded impressive economic growth since the liberalization reforms of the 1990s, translating aggregate gains into equitable poverty reduction has proven difficult, with millions continuing to face multidimensional deprivations beyond mere income shortfalls.